Design Of The Needs Of Educational Services In Gagas Ceria Kindergarten Using Integration Education Quality And Refined Kano - Alif Akbar; Yati Rohayati; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstract The importance of education for children of early age the more years the higher. It is also followeb by growth in the number of Kindergartens in many provinces in Indonesia, especially in West Java Province which has increased in recent years, with a ratio of more growth of private Kindergarten compared to domestic Kindergarten. It suggests that competition of private Kindergarten is more competitive compared with domestic Kindergarten, one of which is TK Gagas Ceria that is an object in this research. TK Gagas Ceria that has A accreditation, but in the last fre years the decreased in applicant from students who previously have taken early childhood education such as Play Group and Toodler in the Gagas Ceria Foundation. The presence of the problem of service Gagas Ceria Kindergarten to make the school need to identify the appropriate service for prospective customers. The study aims to improve the quality of educational services of TK Gagas Ceria using the integration of Education Quality and Refined Kano to identify 21 attributes of the services needs of education needs of TK Gagas Ceria. Based on the results of Education Quality and Refined Kano, there 11 atributes needs to prioritize. The recommendations are formulated based on the results of data processing and analysis involve TK Gagas Ceria sides. These recommendations contain the attributes of services requirements that need to be prioritize as the True Customer Needs. Keywords: Kidergarten,Neeed Analysis, Education Quality, Refined Kano